DIVERSITY, COMPOSITION AND UTILIZATION OF MOLLUSC IN SAPARUA ISLAND, CENTER MOLUCCA - Muhamad Masrur Islami; Idha Yulia Ikhsani; Terry Indrabudi; Iskandar A.H. Pelupessy (Widyariset, 2018)
Saparua Island is one of the islands in the Central Moluccas that has a complete ecosystem, unfortunately records on mollusk research is very limited. The aim of this research is to know the composition, diversity and utilization of mollusk. The objectives of the study are to determine the composition, diversity and utilization of mollusks using square transect and free collection method which conducted on April and September 2016. Water analysis is also done to determine the environmental hydrographic condition. Temperature and salinity indicate the presence of freshwater input through rivers, especially in St-2 2 (Waisisil). Concentrations of nutrients show a fairly high value, ranging from 0.001 to 0.114 mg L-1 for phosphate; 0.012 - 0.023 mg L -1 for nitrate and 0.140 - 0.443 mg L -1 for silicate. There are 641 individual mollusks of 107 species consisting of 85 species of Gastropoda and 22 species of Bivalves. Species found mostly by Littoraria scabra (Littorinidae), Cypraea annulus (Cypreidae), Terebralia sulcata (Potamididae); Clypeomorus battilariaeformis (Cerithiidae); and Nerita chamaeleon (Neritidae). The existing mollusk community has moderate and uniform diversity with low species dominance. There are at least 35 species of mollusks that can be utilized into various commodities such as food products, accessories/decorations and raw materials of drugs.